2002
DOI: 10.1002/rcm.693
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein ions in the range 3000–12000 Th under partial (no discharge) atmospheric pressure chemical ionization conditions using ion trap mass spectrometry

Abstract: A new approach, based on the use of atmospheric pressure chemical ionization ion trap mass spectrometry (APCI-ITMS), but without a corona discharge, was investigated for application to creating and monitoring protein ions. It must be emphasized that APCI is not usually used in protein analysis. In order to verify the applicability of the proposed method to the analysis of proteins, two standard proteins (horse cytochrome c and horse myoglobin) were analyzed. A mixture of the two proteins was also analyzed show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…It must be emphasized that, in these conditions and in the case of proteins, the formation of doubly charged species is privileged and, considering their usefulness in further MS/MS studies (Cramer & Corless, 2001), the observed phenomenon was considered of high interest. Figure 13A,B (Cristoni et al, 2002b) shows the spectra of horse cytochrome c and horse myoglobin, obtained with that technique; in the case of horse cytochrome c, [MþH] ions were observed with good Signal/Noise ratios. The counts per second value of the most abundant signal was 2 Â 10 6 for horse cytochrome c and 5 Â 10 5 for horse myoglobin.…”
Section: Apci Without Corona Dischargementioning
confidence: 99%
See 3 more Smart Citations
“…It must be emphasized that, in these conditions and in the case of proteins, the formation of doubly charged species is privileged and, considering their usefulness in further MS/MS studies (Cramer & Corless, 2001), the observed phenomenon was considered of high interest. Figure 13A,B (Cristoni et al, 2002b) shows the spectra of horse cytochrome c and horse myoglobin, obtained with that technique; in the case of horse cytochrome c, [MþH] ions were observed with good Signal/Noise ratios. The counts per second value of the most abundant signal was 2 Â 10 6 for horse cytochrome c and 5 Â 10 5 for horse myoglobin.…”
Section: Apci Without Corona Dischargementioning
confidence: 99%
“…TEA is used, as described in the ''Deprotonant Agents,'' in order to reduce the protein charge state. Figure 14A,B (Cristoni et al, 2002b) show the spectra obtained; the C-series corresponds to the m/z ions of horse cytochrome c, and the M-series correspond to the ions of horse myoglobin. Figure 14A shows the spectrum of the protein mixture acquired in the positive-ion mode in the m/z 3000-12,000 range without using TEA.…”
Section: Apci Without Corona Dischargementioning
confidence: 99%
See 2 more Smart Citations
“…With such shortcomings, the ionization step may be considered the weakest link and the bottleneck in mass spectrometry at its current stage. Therefore, more vigorous research has been devoted to the study of ion generation in recent years, resulting in several new ionization techniques such as desorption electrospray ionization (DESI) [3], atmospheric pressure photoionization (APPI) [4], laser desorption atmospheric pressure chemical ionization (LD-APCI) [5][6][7], electrospray assisted laser desorption ionization (ELDI) [8,9], laser ablation electrospray ionization (LAESI) [10], no-discharge APCI [11,12], direct analysis in real time (DART) [13], desorption atmospheric pressure chemical ionization (DAPCI) [14], laser induced acoustic desorption (LIAD) [15,16], field-induced droplet ionization (FIDI) [17], and nanostructure-initiator ionization [18]. Among the techniques cited, APPI, ELDI, LAESI, LD-APCI, and LIAD are similar in the sense that they utilize a two-step approach in which desorption and ionization occur during two separate physical processes.…”
Section: Introductionmentioning
confidence: 99%